"Help, I've Been Hacked!": Insights from a Corpus of User-Reported Cyber Victimization Cases on Twitter. (November 2019) - Gratian, Margaret; Bhansali, Darshan; Cukier, Michel; Dykstra, Josiah
Understanding users is critical to develop secure IT systems and effective cybersecurity solutions. Unfortunately, research that analyzes user cybersecurity behaviors and experiences is limited. Motivated by work in public health that relies on Twitter user-reported health conditions, we explore using Twitter to understand user victimization experiences. Observing that users often self-report victimization (Help, I've been hacked!), we construct a corpus of 2, 910 Tweets representing user reports of victimization experiences. We label these reports with information about the affected device or account and the associated consequences, as expressed by the users themselves. We begin to uncover trends in compromise in addition to startling attitudes and behaviors that security practitioners must contend with when developing cybersecurity solutions. To the best of our knowledge, this is one of the first papers to construct and analyze a dataset of cyber victimization user reports.